2015
DOI: 10.1063/1.4914408
|View full text |Cite
|
Sign up to set email alerts
|

Localized surface plasmon resonance anisotropy in template aligned silver nanoparticles: A case of biaxial metal optics

Abstract: Generalized ellipsometry is used to extract the dielectric functions of self-aligned silver nanoparticles on silicon ripple patterns which account for the anisotropic Localized Surface Plasmon Resonance shown by such nanostructures. The biaxial nature of dielectric functions shows its presence through the modified in-plane plasmonic behaviour as compared to the case of random nanoparticles. The nature of in-plane optical coupling and out of plane metallic behavior is further investigated by tuning the interpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Image (c) and image (d) show the SEM images of the deposited silver at an AOI of 70 • . It is clearly visible from both the images that the deposited silver nanoparticles grow by the Volmer Weber mode 13 and in the case of the rippled surface, silver nanoparticles follow the topology of the underlying template as previously observed 6,14 . 2 shows a comparison of the observed atomic density of silver on the flat silica surface and the rippled silica surface for an AOI = 70 • .…”
mentioning
confidence: 55%
“…Image (c) and image (d) show the SEM images of the deposited silver at an AOI of 70 • . It is clearly visible from both the images that the deposited silver nanoparticles grow by the Volmer Weber mode 13 and in the case of the rippled surface, silver nanoparticles follow the topology of the underlying template as previously observed 6,14 . 2 shows a comparison of the observed atomic density of silver on the flat silica surface and the rippled silica surface for an AOI = 70 • .…”
mentioning
confidence: 55%
“…The dielectric functions (Right side) are represented with red and blue lines depict the as-prepared and annealed samples, respectively. Adapted with permission from [43]. © 2015 AIP Publishing LLC as-prepared and annealed cases, albeit, ε z exhibits a behaviour similar to bulk-metal along the z-axis.…”
Section: Anisotropic Specimen: Ag-nanoparticle Arrays On Rippled-simentioning
confidence: 99%
“…Plasmonic optical properties were studied in GLAD deposited indium tin oxide SCTFs decorated with Au nanoparticles using an electroplating process 39 . It was observed that the Au nanoparticles increased the anisotropy of the SCTFs 39,40 . Composites of multiple materials can be achieved, for example, by fabrication of core-shell SCTFs using atomic layer deposition 41 , chemical vapor deposition 42 , or post-growth oxidation 43 .…”
Section: Introductionmentioning
confidence: 99%